Cinacalcet effect on polymorphonuclear leucocytes of kidney transplant patients. (25th March 2013) - Cohen, Gerald; Raupachova, Jana; Borchhardt, Kyra; Hörl, Walter H.
Abstract: Background: Polymorphonuclear leucocytes (PMNLs) play a key role in the nonspecific immune defence. Cinacalcet reduces serum calcium levels in kidney transplant recipients with mineral bone disorder associated with chronic kidney disease. We investigated essential functions of PMNLs of kidney transplant recipients with and without hypercalcaemia and with and without cinacalcet therapy. Subjects and methods: Oxidative burst, phagocytosis, apoptosis and intracellular calcium concentrations of PMNLs from normocalcaemic kidney transplant patients without (KT‐NC) or with cinacalcet intake (KT‐NC/CI), hypercalcaemic kidney transplant patients (KT‐HC) and healthy subjects (HS) were investigated. Results: Stimulation of oxidative burst of PMNLs from KT‐HC patients by phorbol‐12‐myristate‐13‐acetate or Escherichia coli was significantly attenuated compared with PMNLs from KT‐NC, KT‐NC/CI and HS. Apoptosis of PMNLs from KT‐HC patients was significantly decreased compared with cells from KT‐NC, KT‐NC/CI and HS. Apoptosis correlated significantly with serum calcium concentrations. Intracellular calcium concentrations and phagocytosis of PMNLs did not differ between groups. Conclusions: Our data indicate that stimulation of PMNL oxidative burst and apoptosis is significantly diminished in kidney transplant patients with hypercalcaemia, while kidney transplant patients with serum calcium levels normalized by cinacalcet have normal PMNL functions despite immunosuppressive therapy.